Penerapan Aplikasi Green Economy Digital Nitipsampah dalam mengolah limbah sampah rumah tangga di Cluster Winola Kabupaten Banyuasin Sumatera Selatan - Wulandari , Try; Kholik , Abdul; Pratiwi , Mariska Putri (IKRA-ITH ABDIMAS, 2023)
The research results indicate that the implementation of the digital Green Economyapplication "Nitipsampah" has successfully increased public awareness in Cluster Winolaregarding household waste management. The use of this application has also streamlined theprocess of waste collection, sorting, and delivery to appropriate processing facilities. Thepositive impacts achievable through this application include waste reduction, resourceconservation, and an increase in the utilization of waste as a valuable resource. Therefore, thisresearch concludes that the implementation of the digital Green Economy application"Nitipsampah" has significant potential in supporting sustainable household waste management efforts in Cluster Winola and could serve as a relevant model for similar areas throughout South Sumatra. This reserach also provides and initial perspective on the role technology in supporting sustainable practices within the contex of a green economy